2023
DOI: 10.3390/su151813378
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Residual Municipal Solid Waste Composition from Rural and Urban Areas: A Step toward the Optimization of a Waste Management System for Efficient Material Recovery

Maria Triassi,
Bruna De Simone,
Paolo Montuori
et al.

Abstract: Residual municipal solid waste (RMSW) is a rapidly expanding problem worldwide and a good waste management system could reduce concerns about its correct treatment. The purpose of this study was to characterize RMSW from urban and rural areas with the ultimate goal of estimating the recycling potential of the identified fractions and implementing waste collection and recovery methods according to the type of area that generates them. A direct sampling campaign of RMSW was performed. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…As the smallest-sized city, Magelang generates a relatively insignificant amount of plastic waste from consumer products, such as PET bottles or other rigid plastic food packaging (WBC3). This aligns with a previous study by Triasi et al, which found that urban areas tend to have a higher volume of recyclable waste, including plastic, than organic waste, compared to areas with lower population densities [128]. This trend is also attributed to the community's preference for home cooking, a practice where many cooking ingredients purchased from the market are commonly wrapped in transparent soft plastics (WBC3).…”
Section: Plastic Waste Compositionsupporting
confidence: 90%
See 2 more Smart Citations
“…As the smallest-sized city, Magelang generates a relatively insignificant amount of plastic waste from consumer products, such as PET bottles or other rigid plastic food packaging (WBC3). This aligns with a previous study by Triasi et al, which found that urban areas tend to have a higher volume of recyclable waste, including plastic, than organic waste, compared to areas with lower population densities [128]. This trend is also attributed to the community's preference for home cooking, a practice where many cooking ingredients purchased from the market are commonly wrapped in transparent soft plastics (WBC3).…”
Section: Plastic Waste Compositionsupporting
confidence: 90%
“…This high prevalence of soft plastics may also be linked to the city's local fashion industry (see Table 1), which requires a significant amount of plastic packaging [126]. Furthermore, several previous studies have demonstrated a positive correlation between a city's size, population growth, and income and its MSW consumption [127][128][129]. However, studies on plastic waste composition and its relationship to city characteristics remain limited.…”
Section: Plastic Waste Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban areas with high population density tend to have more waste management and recycling infrastructure in contrast to rural areas that have less infrastructure and may not recycle at all. 56 In the case of centralized sorting, material recovery facilities (MRFs) take in mixed recyclable waste streams and separate plastic materials by polymer type. Currently, of plastic types, most US MRFs only target PET and HDPE with a particular focus on bottles and other rigid forms.…”
Section: Upstream Assumptionsmentioning
confidence: 99%
“…Because a comprehensive knowledge of the MSW composition enables effective, economical, and environmentally friendly MSWM systems for efficient material recovery (Faisal et al, 2019;Triassi et al, 2023), this study aims to develop a structured approach for MSW quantification. It also seeks to determine the composition of the MSW, identify current MSWM practices, ascertain the energy contents of the MSW generated in the Aba metropolis, and propose sustainable MSWM techniques based on circularity.…”
Section: Introductionmentioning
confidence: 99%